Challenges in defining and measuring social resilience - Mahler, Balázs (Észak-magyarországi Stratégiai Füzetek, 2024)
Over the past two decades, resilience has gained considerable popularity in both social and economic sciences, reinforced by the effects of various economic and social shocks and the pandemic that has spread worldwide. On the other hand, more and more detailed and extensive studies have been launched on the various types of resilience (social, economic, ecological, etc.), which, in addition to the undoubtedly useful scientific results, have highlighted the elusive nature of the phenomenon and the lack of a centripetal force to channel the various lines of research in a single direction and unify the various interpretative frameworks. The paper attempts to provide a conceptual overview of one type of resilience, social resilience, based on the available theoretical framework. With the help of previous research results, I will define a set of indicators for this concept to test and verify it in the context of empirical research. Refining the indicator set and the definition also provides an opportunity to distinguish between different types of resilience partially, thus contributing to a more accurate scientific understanding. The added value of the paper is that some of the indicator groups have been tested empirically, thus demonstrating the scientific value of the method.